Endothelial GABBR2 Regulates Post-ischemic Angiogenesis by Inhibiting the Glycolysis Pathway - Zhang, Hongze; Zhou, Hong; Yuan, Jianying; Nan, Yong; Liu, Jingquan (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Angiogenesis post-ischemia plays an essential role in preventing ischemic damage to tissue by improving the blood recovery. Determining the regulatory mechanism of ischemic angiogenesis, therefore, could provide effective therapeutics for ischemic injury. Materials and Methods: The RNA sequencing (RNA-seq) database was used to predict the association of gamma-aminobutyric acid type B receptor subunit 2 (GABBR2) with endothelial-specific expression. The role of GABBR2 in angiogenesis was verified in vitro by downregulating GABBR2 in human umbilical vein endothelial cells (HUVECs) with lentiviral vectors. Besides, the in vivo effect of GABBR2 on the blood recovery of an ischemic hindlimb was demonstrated by establishing a hindlimb ischemia model in normal and GABBR2 adenoviral vector-infected mice. Then, the mobilization of endothelial progenitor cells (EPCs) in peripheral blood post-ischemia was determined by flow cytometry. Finally, the XF analyzer and Western blot were used to determine the effect of GABBR2 on endothelial metabolism. Results: The RNA-seq results indicated a strong association between GABBR2 and endothelial revascularization, and the upregulation of GABBR2 was detected in both hypoxia-treated HUVECs and ischemic mouse hindlimb. Hypoxia treatment for 6 h increased the proliferation, migration, and tube formation of HUVECs, which were inhibited by GABBR2 knockdown. Additionally, GABBR2 downregulation significantly decreased the blood flow recovery of mouse ischemic hindlimb. The expressions of the EPC markers CD34+ and CD133+ significantly decreased in the peripheral blood in hindlimb post-ischemia. Mechanically, glycolysis-dominated metabolism of HUVECs was compromised by GABBR2 knockdown. Evidences of the decreased expressions of HKII, PFKFB3, and PKM1 also supported the compromised glycolysis induced by GABBR2 downregulation. Conclusion: Our study demonstrated that GABBR2 regulated angiogenesis post-ischemia by inhibiting the glycolysis pathway.